Analisis Manajemen Badan Usaha Milik Desa (BUMDESA) â€œHanyukupiâ€ Desa Ponjong Kecamatan Ponjong Kabupaten Gunungkidul - Nilawati, Evi (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2018)
This research is about Management Analysis Â Village Owned Enterprise â€œHanyukupiâ€, aims to know how actualization of the management of Village Owned Enterprise â€œHanyukupiâ€. The research used descriptive qualitative method. Informen were taken by purposive sampling and data were obstained through secondary data, observation, and indepth interviews. The result showed that Â Village Owned Enterprise â€œHanyukupiâ€ has implemented the standard principles of management are planning, organizing, staffing, leadership, and controlling. Management of planning has been implemented by preparing annual working plan. Â Organizing management were done by preparing article of association Â and by the laws as guideline for the members. TheÂ  organization structured the organization as the guidance to mobilized all component of organization. Staffing management were done through placement Â personnel based on the right man on the right place, recruitment, and development the carreer. LeadershipÂ  management were done by administering the functions of leadership implemented by the leader. Controlling management were done through effort to support Village Owned Enterprise evaluated attainment the performance of organization with effectiveness and efficient. In order to realization sustainable improvement the management of Village Owned Enterprise need Â effort Â improvement to be good performance, professional, and accountable withÂ  preparing vision, mission, and goalsÂ  intoÂ  Bussiness Strategic Plan.